2020
DOI: 10.20546/ijcmas.2020.910.373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levels of Phosphorus and Zinc on Growth and Yield of Greengram (Vigna radiata L.)

Abstract: The present investigation titled "Effect of levels of phosphorous and zinc on growth and yield of Greengram (Vigna radiata L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
11
4
0
Order By: Relevance
“…Similarly higher yield attributes and yield were noticed with the combined foliar spray of micro nutrients with zinc attributed to optimum availability of nutrients for luxurious crop growth and efficient partitioning of assimilates from source to sink. The similar results were reported by Masih et al [12].…”
Section: Test Weight (G)supporting
confidence: 92%
See 1 more Smart Citation
“…Similarly higher yield attributes and yield were noticed with the combined foliar spray of micro nutrients with zinc attributed to optimum availability of nutrients for luxurious crop growth and efficient partitioning of assimilates from source to sink. The similar results were reported by Masih et al [12].…”
Section: Test Weight (G)supporting
confidence: 92%
“…It might be due to its direct influence on auxin production which in turn enhanced the elongation processes of plant development. The similar results were reported by Masih et al [12].…”
Section: Stover Yield (T/ha)supporting
confidence: 92%
“…Application of phosphorus help in efficient utilization of nutrients, which resulted in attaining better crop canopy and further increased absorption and utilization of radiant energy resulting in higher effective and total number of nodules per plant. These results are confirmed with the findings of other researcher Patel et al, [8] and Ashish Masih et al, [9] who reported that application of phosphorus increased the number of nodules per plant.…”
Section: Number Of Nodulessupporting
confidence: 91%
“…Similarly higher yield attributes and yield were noticed with the combined foliar spray of micro nutrients with zinc attributed to optimum availability of nutrients for luxurious crop growth and efficient partitioning of assimilates from source to sink. Higher stover yield of mungbean might be due to direct influence of zinc on auxin production which in turn enhanced the elongation processes of plant development" [2,3,4,5,6,7,8,9]. Similar results higher yield and quality on maize crop was given by Satdev et al, [10], and Peddapuli et al [11] in maize.…”
Section: Resultsmentioning
confidence: 55%